Integrated risk of pandemic Covid-19 impacts, resilience and recommendations - Goyal, Manish Kumar; Gupta, Anil Kumar 1954- (Disaster resilience and green growth, 2020)
In light of the novel corona virus outbreak in December 2019 and its subsequent impact on entire world as a global pandemic, the book attempts to provide integrated risk assessment on Covid -19 like pandemics, as well as to understand the societal, environment and economic impact of the outbreak in various sectors of development. It covers fundamental factors of global disease outbreaks and its coverage as major disaster through the complexity and severity of consequences, illustrating the dimensions of low frequency high intensity disasters. It brings together broad range of topics including basic concepts, isolation measure, role of governance and key technical advancements for containing the diseases. In addition, it also covers resilience analysis towards the impacts such outbreaks have on bio-diversity, ecosystem services and agricultural food production. It defines key exit strategies from the lessons learned and success stories of historical disease outbreaks. The book is presented in four parts, where part 1 familiarizes with fundamentals; part 2 focuses on integrated risk assessments; part 3 focuses on various measures and strategies of resilience; and part 4 suggests key lessons and recommendations. The book is a useful reading reference for scientific community, policy makers and professionals across the domains of health, environment, disasters and sustainable development. Book is specifically beneficial for postgraduate students, researchers, planners and field professionals